2014
DOI: 10.1111/jgh.12547
|View full text |Cite
|
Sign up to set email alerts
|

Different roles for p16INK4aRb pathway and INK4a/ARF methylation between adenocarcinomas of gastric cardia and distal stomach

Abstract: There were differences in p16(INK) (4a) -Rb immunotypes and INK4a/ARF methylation between two entities, indicating that cardia adenocarcinoma may be different in cell proliferation, differentiation, and gene biomarkers compared with distal gastric adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Similar molecular abnormalities also occur in gastric cardia neoplasia (37)(38)(39)(40)(41)(42), supporting the contribution of TP53 and CDKN2A to diverse types of adenocarcinogenesis involving the GEJ region. In agreement with these static observations, our dynamic model establishes that TP53/CDKN2A inactivation directly causes biologic and molecular features consistent with GEJ neoplastic progression.…”
Section: Discussionmentioning
confidence: 59%
“…Similar molecular abnormalities also occur in gastric cardia neoplasia (37)(38)(39)(40)(41)(42), supporting the contribution of TP53 and CDKN2A to diverse types of adenocarcinogenesis involving the GEJ region. In agreement with these static observations, our dynamic model establishes that TP53/CDKN2A inactivation directly causes biologic and molecular features consistent with GEJ neoplastic progression.…”
Section: Discussionmentioning
confidence: 59%
“…Likewise, CDKN2A is inactivated in more than 80% of BE and EAC tissues (34)(35)(36). Similar molecular abnormalities also occur in gastric cardia neoplasia (37)(38)(39)(40)(41)(42), supporting the contribution of TP53 and CDKN2A to diverse types of adenocarcinogenesis involving the GEJ region. In agreement with these static observations, our dynamic model establishes that TP53/CDKN2A inactivation directly causes biologic and molecular features consistent with GEJ neoplastic progression.…”
Section: Discussionmentioning
confidence: 72%
“…An early study showed that about 50% of GC samples were detected with the loss of p16 expression ( 36 ). Interestingly, the expression of p16 in distal gastric carcinomas was higher than that in gastric cardia carcinomas ( 40 ). In GC, abnormal methylation of CpG islands in the promoter region of p16 downregulated p16 ( 47 ).…”
Section: Upstream Regulators Of the Rb-e2f Pathway In Gastric Cancermentioning
confidence: 91%